2020
DOI: 10.1017/s1368980019003938
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to address anaemia among pregnant and lactating women in India: a formative research study

Abstract: Objective:Over half of pregnant women in India are affected by anaemia, which can lead to premature birth, low birth weight and maternal and child mortality. Using formative research, we aimed to understand social and cultural factors around iron and folic acid (IFA) supplement provision and adherence to identify potential strategies for improving adherence and behaviours to prevent and treat anaemia among pregnant and lactating Indian women.Design:In-depth interviews and focus group discussions with women and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 41 publications
1
13
1
2
Order By: Relevance
“…Low intake of iron-rich foods together with poor bioavailability, chronic infection, malaria and intestinal helminths, and higher requirement related to menstruation lead to iron deficiency (Ampiah et al, 2019;Jamnok et al, 2020).Educational status, age, access to healthcare, socio-economic status, frequency of pregnancy, availability and consumption of nutrients/diet, and place of residence are identified as associated factors for being anaemic (Sharma et al, 2020). Anaemia affects individuals in the different periods of the life cycle but is most common in lactating mothers, pregnant women and adolescent girls as well (Ayensu et al, 2020;Williams et al, 2020). Nearly one-fifth of the total maternal deaths are resulted directly due to anaemia.…”
Section: Introductionmentioning
confidence: 99%
“…Low intake of iron-rich foods together with poor bioavailability, chronic infection, malaria and intestinal helminths, and higher requirement related to menstruation lead to iron deficiency (Ampiah et al, 2019;Jamnok et al, 2020).Educational status, age, access to healthcare, socio-economic status, frequency of pregnancy, availability and consumption of nutrients/diet, and place of residence are identified as associated factors for being anaemic (Sharma et al, 2020). Anaemia affects individuals in the different periods of the life cycle but is most common in lactating mothers, pregnant women and adolescent girls as well (Ayensu et al, 2020;Williams et al, 2020). Nearly one-fifth of the total maternal deaths are resulted directly due to anaemia.…”
Section: Introductionmentioning
confidence: 99%
“…The body is capable of restoring iron reserves in 4-5 years. If a woman anticipates an earlier pregnancy, she will inevitably develop anemia [22]. A comprehensive approach to preventing anemia in women of reproductive age is therefore required to improve the hematological status, as also health indicators of mother and child [17], [23].…”
Section: Discussionmentioning
confidence: 99%
“…Folate de ciency has been linked to neural tube defects (NTD) (11,12), whereas its impact on other severe pregnancy outcomes is inconclusive. Some studies provide support to maternal MTHFR 677TT genotypes, together with maternal circulating folate and homocysteine (hcy) concentrations are independent risk factors for small gestational age (SGA) (13)(14)(15). Other observational studies found no direct association between low folate levels and pregnancy complications (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%